LoRa on the bus: Time and location monitoring system for P2P buses - Bañez, John Herald Angeles (Animo Repository, 2023)
The current P2P bus service system in the Philippines rarely provides information regarding delays and changes in schedules which have left passengers waiting in long queues with no assurance of when the next bus will arrive. Thus, a developed system is needed to monitor the location of P2P buses to provide the necessary information to commuters. This paper focused on the design and implementation of a LoRa system with multi-hop capabilities that can track the movement of P2P buses and provide necessary information such as location and speed for monitoring purposes. The system utilized a RAK7246G WisGate Developer D0 for the gateway, Arduino MKR WAN 1300 boards for the end nodes, and U-Blox GPS NEO6MV2 Flight Control Module2 for the GPS module. The system was then programmed using the Arduino IDE to parse data from the GPS module, to send packets to the gateway, and to receive packets from other nodes either broadcasting the message to other nodes or sending directly to the gateway based on the process of concurrent transmission protocol. A dashboard was also developed using Node-RED. Preliminary tests showed that the speed of the node had no significant effect on the maximum range for both note-to-gateway and node-to-node transmissions. The complete system tests consisted of three test scenarios that were performed by the group to test the functionality and the multi-hop capabilities of the system. Each test provided consistent results with speeds and ETAs of nodes being within the ± 5 km/h and ± 5 minute difference respectively when compared to the actual speed and travel time using a third party application. The dashboard was also able to display the status of the bus whether it is in transit or not. Results also showed that the system was able to effectively perform up to two node-to-node hops when the packet transmitted was outside the range of the gateway. For LOS conditions, minimal errors with packet delivery to the gateway were observed, while occasionally successful but with distorted packets were observed for Non-LOS conditions.